LANDSLIDE MONITORING IN A BUILT-UP AREA - Černoch, Petr; Černoch, Petr; Koštál, Jiří; Podojil, Adam (České vysoké učení technické v Praze, 2021)
The article deals with the evaluation and comparison of measured data from geotechnical monitoring of a gabion wall and an adjacent slope. In 2015, new anomalous phenomena related to deformations and a shift in the area of previously activated landslide were recorded on some monitoring elements in the area of the gabion wall. Measurements carried out in previous stages had revealed the re activation of landslides, probably due to a significant rise in groundwater levels, whose fluctuation has been up to 3 m. A proper evaluation of the obtained results cannot be quantified without the determination of warning status or without a stability calculation. Only the trend and magnitude of the measured values can be evaluated.